METHODOLOGY FOR CLASSIFICATION OF EUCALYPTUS CLONES FOR SOLID WOOD - França, Morgana Cristina; Marchesan, Raquel; Carvalho, Douglas Edson; Pereira da Rocha, Márcio; Klitzke, Ricardo Jorge; Moreira da Silva, José Reinaldo (Floresta, 2023)
The aim of this study was to develop scoring tables based on log quality, sawn wood quality and physical and mechanical properties for the selection of Eucalyptus clones for the production of solid wood. Five clones were selected, being three hybrids of Eucalyptus grandis x Eucalyptus urophylla, a clone of Eucalyptus urophylla and a clone of Eucalyptus grandis, 10 years of age. For the classification of the best clone, two scoring tables were created, one considering the result of the statistical analysis and the other the absolute values. With the tables it was possible to classify the clones according to the analyzed parameters (quality of the logs, quality of the sawn wood, sawn wood yield, physical properties and mechanical properties) separately and to observe more clearly some factors that directly influence the results. The clone of Eucalyptus grandis (clone 4) presented the best results, being classified as of superior quality in relation to the others for the production of solid wood. Thus, the scoring tables using statistical analysis or absolute values proved to be useful and applicable tools for the qualitative classification of clones.